Setor terciário: formalidade e informalidade: algumas especificidades da (re)produção do espaço urbano de Bayeux-PB - Silva, Ricélia Maria Marinho da (2006)
This work has as study object the tertiary sector and (the re)production of the urban space of Bayeux-PB. For in such a way, one became necessary to the construction of a theoretical boarding that context the national reality, to be able itself to understand the reality local. This way to construct allowed an opening of the field of vision how much to the relevance of if ahead studying the tertiary sector and its weight of the current configuration of the society in a country as Brazil, e especially in a city of a State northeastern, as it is the case of Bayeux. The theoretical boarding had as base the two circuits of the urban economy, the productive reorganization and the transformations in the world of the work, as well as, the space organization and the distinction between the economic and social space of the tertiary activities, from the logic of functioning of the establishments: the regulation. Besides working with referring official data to the tertiary sector, the empirical study it had as reference one hundred and sixty and establishments tertiary, located in four axles of circulation of the city of Bayeux - PB, which are: Av. Liberdade, Av. Engenheiro de Carvalho, Av. Francisco Marques da Fonseca and Av. Marechal Rondon, that they had appeared in such a way stimulated for the processes of urbanization and industrialization lived deeply from years 70 in the "Great João Pessoa" how much, in the countries of the underdeveloped capitalist world, as Brazil. Being thus, the objective of the work was to study the tertiary sector and its relation with (the re)production of the urban space, standing out the functioning logic